Evaluation of biogas production as a source of renewable energy though co-digestion of agricultural residues and poultry manure - Göl, Nefise Pınar. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2012., 2012)
The need for alternative energy sources for Turkey is obvious. Biogas production via agricultural residues and manure seems to be an advantageous option for Turkey, since the main income is generally provided from the agro industry. Through anaerobic digestion of agricultural residues and poultry manure, wastes will be properly disposed and biogas, which is a clean and sustainable source of energy, will be continuously recovered. As a renewable energy source, biogas production from agro industrial wastes is a useful management option, energy independent and environmentally friendly. Biogas can be used for production of heat, electricity, as fuel in vehicles and as a substitute of natural gas. The objective of this study was to investigate the potential of biogas generation via anaerobic co-digestion of the chosen agricultural residue -sunflower residues- and poultry manure. Mixtures composed of different amounts of substrates were prepared and digested under anaerobic conditions with the addition of inoculum culture (seed sludge), using batch tests under mesophilic laboratory conditions. If the potential of biogas production from co-digestion of poultry manure and agricultural residue can be determined by batch-tests, then it will be possible to calculate the theoretical amount of energy that can be produced from these substrates, since the production amounts of agricultural residue and manure are known. According to the results obtained, it will be possible to use these substrates for the continuous lab scale studies or larger scale commercial agricultural biogas plants. Within the scope of this study, several compositions of sunflower residue, poultry manure and inoculum mixtures were elaborated and digested under mesophilic conditions. However reliable methane production could be only achieved in the first two trials. This outcome is mainly attributed to the low biodegradability of the sunflower residues thus further studies, including pretreatment methods are recommended.
Keywords: Biogas.; Sewage -- Purification -- Anaerobic treatment.